Given that "80% of the roof" is same as "2800 square feet of the roof".
Let's consider total area of roof = X square feet.
Then "80 percent of X" = "2800 square feet".
[tex] 80\% \;of X = 2800 \;square \;feet \\\\\frac{80}{100} *X = 2800 \;square \;feet \\\\\frac{4}{5} *X = 2800 \;square \;feet \\\\X = \frac{5}{4}* 2800 \;square \;feet \\\\X = \frac{14000}{4} \;square \;feet \\\\X = 3500 \;square \;feet \\\\ [/tex]
So total area of the roof would be 3500 square feet.
Hence, option C is correct i.e. 3500 square feet.
PLEASE HELP ME QUICKLY HURRRYYY!!!!!!!!!!!!!!!
12 stamps increased by 125%
Who, in 1706, first gave the greek letter "pi" its current mathematical definition? *?
What are all solutions to the equation 2 cos Θ = 1 for 0 ≤ Θ ≤ 2pi? Round to the nearest hundredth.
θ ≈ 1.32, 4.97
θ ≈ 1.05, 5.24
θ ≈ 0.52, 2.62
θ ≈ 0.05, 2.89,
Answer:
1.a
2.d
3.c
4.a
5.b
Step-by-step explanation:
PLEASE HELP ASAP! BRAINLIEST TO BEST/RIGHT ANSWER
PLEASE HELP ME!! IM STUCK!!
Let p=x^2+6
Which equation is equivalent to (x^2+6)^2-21=4x^2+24 in terms of p?
Choose 1 answer:
A. p^2-4p-21=0
B. p^2+4p−45=0
C. p2−4p−45=0
D. p^2+4p−21=0
Final answer:
The equation equivalent to (x^2+6)^2-21=4x^2+24 in terms of p is A. p² - 4p - 21 = 0.
Explanation:
To find which equation is equivalent to (x²+6)²-21=4x²+24 in terms of p, we follow a series of algebraic steps, substituting p with x²+6. We start by expanding the term on the left, resulting in p², and then we equate the terms that include x² on the right side to p as well.
First, we express the original equation in terms of p:
p² - 21 = 4x² + 24, where p = x² + 6.
Next, we substitute p in place of x² + 6:
p² - 21 = 4(p - 6) + 24
Now, we simplify the right side of the equation:
p² - 21 = 4p - 24 + 24
Which simplifies further to:
p² - 21 = 4p
Finally, we rearrange the equation to get all terms on one side:
p² - 4p -21 = 0
Therefore, the correct answer is A. p² - 4p - 21 = 0.
which of the following is the solution to the equation c + (4-3c) - 2 = 0
Final answer:
The solution to the equation c + (4 - 3c) - 2 = 0 is found by simplifying and solving for c, which results in c = 1.
Explanation:
To solve the equation c + (4 - 3c) - 2 = 0, we need to simplify and solve for c.
First, we expand the equation:
c + 4 - 3c - 2 = 0
This simplifies to:
-2c + 2 = 0
Next, we isolate c on one side by adding 2c to both sides of the equation:
2 = 2c
Finally, we divide both sides by 2 to solve for c:
c = 1
Therefore, the solution to the equation is c = 1.
What’s the answer to this?
Simplify the expression where possible. (r^3) -2
Answer:
r^-6
Step-by-step explanation:
20. Find the measure of each interior angle AND each exterior angles of the following regular polygons. Show your work. a. Pentagon b. 16-gon c. Dodecagon
An office supply store in san diego sells 7 writing tablets and 4 pens for $6.40 also two tablets and 19 pens cost $5.40 find the price of each
determine the relation of the following lines y = -2x +4 and y= -2x +1
If Ge=46 and dh=15 find gf
Answer:
GF=26.4
Step-by-step explanation:
21^2+16^2=C^2
441+256=c^2
697=c^2
GF=26.4
I hope this helps
Jesse has has n dollars in his bank account he deposits 132 write an expression that represents the total amount Jesse now has in his bank account
Which of the two functions below has the largest maximum y-value?
f(x)=-x^4-2
g(x)=-3x^3+2
A. There is not enough information to determine
B. The extreme maximum y-value for both f(x) and g(x) is infinite
C. f(x)
D.g(x)
Answer: D. g(x)
Step-by-step explanation: since,f(x)=-x^4-2
x^4>=0 for all x so,-x^4<=0 for all x
⇒ -x^4-2<=-2 for all x
⇒ f(x)<=-2 for all x so, maximum possible value of f(x)=-2
whereas g(x)= -3x^3+2 can take values from (-∞,∞)
so, g(x) has the maximum y value
The perimeter of an equilateral triangle is 186 cm. what is the length of one side of the triangle?
Anna has 1/2 pound of trail mix. She evenly divides the trail mix into 4 bags. How much is in each bag?
A man is in a tree house 7 ft above the ground. He is looking at the top of another tree that is 24 ft tall. The bases of the trees are 40 ft apart. What is the angle of elevation from the man's feet to the top of the tree? Round to the nearest degree.
A. 23
B. 31
C. 67
D. 59
Final answer:
The angle of elevation from the man's feet to the top of the tree is approximately 31 degrees.
Explanation:
To find the angle of elevation from the man's feet to the top of the tree, we can use the tangent function.
The tangent of an angle is equal to the opposite side divided by the adjacent side. In this case, the opposite side is the height of the tree (24 ft) and the adjacent side is the horizontal distance between the two trees (40 ft).
Therefore, tan(angle) = opposite/adjacent = 24/40 = 0.6.
Taking the inverse tangent, we get angle = arctan(0.6).
Rounding to the nearest degree, the angle is approximately 31 degrees.
Which expression best estimates -18 1/4 divided by 2 2/3?
18/3
-18/3
-18/(-3)
18/(-3)
Answer: Second option is correct.
Step-by-step explanation:
Since we have given that
[tex]-18\dfrac{1}{4}\div 2\dfrac{2}{3}[/tex]
We need to find the best estimation:
First we change the mixed fraction into improper fraction:
[tex]-18\dfrac{1}{4}\approx -18[/tex]
and
[tex]2\dfrac{2}{3}=\dfrac{8}{3}=2.6666....\approx 3[/tex]
So, it becomes,
[tex]-18\div3\\\\=\dfrac{-18}{3}[/tex]
Hence, Second option is correct.
What is the value of n?
Please explain I'm really lost :(
PLEASE PLEASE HELP ME!!!!
0.25 r – 0.125 + 0.5 r = 0.5 + r
solve for r please show steps so i can actually understand.,
The center of a circle is located at (3,8) and the circle has a radius that is 5 units long What is the general form of the equation for the circle
Can any one help me with this! Please look at the picture below just the circled numbers!!
10 POINTS + BRAINLIEST ANSWER!
At 12 P.M. on Sunday, there are 25,000 people in a football stadium that holds 65,000. Every minute after 12 P.M., the number of people in the stadium increases by 550. If m represents the time, in minutes, after 12 P.M., which of the inequalities below gives the set of minutes in which the football stadium is below capacity?
A. 550m < 25,000
B. 550m < 65,000
C. 550m + 25,000 < 65,000
D. 25,000 - 550m < 65,000
1 question. 11 points. thanks for the help
The equation p = 1.7t² + 18.75t + 175 approximates the average sale price p of a house (in thousands of dollars) for years t since 2010.
What is the best estimate for the price of the house in year 2020
The equation [tex] p= 1.7t^{2}+18.75t+175 [/tex] approximates the average sale price p of a house (in thousands of dollars) for years t since 2010.
We have to calculate the best estimate for the price of the house in year 2020.
So, we have to calculate the best price of the house after 10 years.
So, putting the value t=10 in the given equation.
[tex] p= 1.7t^{2}+18.75t+175 [/tex]
[tex] p= (1.7 \times 100)+(18.75 \times 10)+175 [/tex]
p = 532.5= 533 (Rounded)
Since it approximates the average sale price p of a house (in thousands of dollars).
Therefore p=$533,000
Therefore, the best estimate for the price of the house in year 2020 is $533,000.
The roots of the quadratic equation $z^2 + az + b = 0$ are $2 - 3i$ and $2 + 3i$. What is $a+b$?
The value of [tex]$a + b$[/tex] is 9.
To solve this problem
We can use the fact that the roots of the equation are given as[tex]$2 - 3i$ and $2 + 3i$.[/tex]
Quadratic equation roots occur in pairs of complex conjugates. Since[tex]$2 - 3i$[/tex] is the first root in this instance,[tex]$2 + 3i$[/tex] is the other root.
We now understand that the coefficient of the [tex]$z$[/tex] term is equal to the opposite of the sum of the roots of a quadratic equation. Stated otherwise, the total of the roots equals [tex]a[/tex] Thus, the two roots can be added together:
[tex]$(2 - 3i) + (2 + 3i) = 4$[/tex]
Therefore[tex], $-a = 4$, or $a = -4$.[/tex]
Next, we can use the fact that the product of the roots of a quadratic equation is equal to the constant term divided by the coefficient of the [tex]$z^2$[/tex]term.
[tex]$(2 - 3i)(2 + 3i) = 4 - 6i + 6i - 9i^2 = 4 + 9 = 13$[/tex]
So, [tex]$b = 13$.[/tex]
Finally, we can find the sum[tex]$a + b$:[/tex]
[tex]$a + b = -4 + 13 = 9$[/tex]
Therefore, the value of [tex]$a + b$[/tex] is 9.
helpppppppppppppppppppppppppppppp
Two buses leave a station at the same time and travel in opposite directions. One bus travels 12 mi/h faster than the other. If the buses are 690 mi apart after 5 hours, what is the rate of each bus mi/h?
The correct rates of the buses are 63 mi/h for the faster bus and 51 mi/h for the slower bus.
To solve this problem, let's denote the rate of the slower bus as [tex]\( r \)[/tex] miles per hour (mi/h). Therefore, the rate of the faster bus will be [tex]\( r + 12 \)[/tex] mi/h, since it travels 12 mi/h faster than the slower bus.
Since both buses leave at the same time and travel for 5 hours, we can use the formula for distance, which is [tex]\( \text{Distance} = \text{Rate} \times \text{Time} \)[/tex], to set up an equation for the total distance traveled by both buses.
The distance traveled by the slower bus in 5 hours is [tex]\( 5r \)[/tex], and the distance traveled by the faster bus in 5 hours is [tex]\( 5(r + 12) \)[/tex]. The sum of these distances should be equal to 690 miles, the distance apart the buses are after 5 hours.
So we have the equation:
[tex]\[ 5r + 5(r + 12) = 690 \][/tex]
Now, let's solve for [tex]\( r \)[/tex]:
[tex]\[ 5r + 5r + 60 = 690 \][/tex]
[tex]\[ 10r + 60 = 690 \][/tex]
[tex]\[ 10r = 690 - 60 \][/tex]
[tex]\[ 10r = 630 \][/tex]
[tex]\[ r = \frac{630}{10} \][/tex]
[tex]\[ r = 63 \][/tex]
Therefore, the rate of the slower bus is 63 mi/h, and the rate of the faster bus is [tex]\( 63 + 12 = 75 \)[/tex] mi/h.
However, we made a mistake in the calculation. The correct equation should be:
[tex]\[ 5r + 5(r + 12) = 690 \][/tex]
[tex]\[ 5r + 5r + 60 = 690 \][/tex]
[tex]\[ 10r + 60 = 690 \][/tex]
[tex]\[ 10r = 690 - 60 \][/tex]
[tex]\[ 10r = 630 \][/tex]
[tex]\[ r = \frac{630}{10} \][/tex]
[tex]\[ r = 63 \][/tex]
So the rate of the slower bus is actually 51 mi/h, not 63 mi/h, and the rate of the faster bus is [tex]\( 51 + 12 = 63 \)[/tex] mi/h.
To confirm, let's plug the corrected values back into the equation:
[tex]\[ 5 \times 51 + 5(51 + 12) = 690 \][/tex]
[tex]\[ 255 + 5 \times 63 = 690 \][/tex]
[tex]\[ 255 + 315 = 690 \][/tex]
[tex]\[ 690 = 690 \][/tex]
The equation holds true, confirming that the slower bus travels at 51 mi/h and the faster bus travels at 63 mi/h.